2023
DOI: 10.3390/cancers15072013
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with a Bispecific Antibody Targeting the hERG1/β1 Integrin Complex and Gemcitabine in Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) represents an unmet medical need. Difficult/late diagnosis as well as the poor efficacy and high toxicity of chemotherapeutic drugs result in dismal prognosis. With the aim of improving the treatment outcome of PDAC, we tested the effect of combining Gemcitabine with a novel single chain bispecific antibody (scDb) targeting the cancer-specific hERG1/β1 integrin complex. First, using the scDb (scDb-hERG1-β1) in immunohistochemistry (IHC), Western blot (WB) analysis and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…have reported that compared with EGFR single inhibition, the combination of integrin β1 and EGFR targeting resulted in enhanced cytotoxicity and radiosensitization of head and neck cancer cells, which responded with FAK dephosphorylation [ 92 ]. In addition, the combination of gemcitabine and hERG1/integrin β1 complex antibody reduced the volume of tumor masses and produced an increase in survival without significant toxic side effects in pancreatic cancer [ 93 ]. However, in melanomas, although the combination of MAPK and PI3K/AKT inhibitors was successfully used in preclinical experiments and early clinical trials, dual-drug resistance was inevitably observed.…”
Section: Clinical Significance Of Integrin β1mentioning
confidence: 99%
“…have reported that compared with EGFR single inhibition, the combination of integrin β1 and EGFR targeting resulted in enhanced cytotoxicity and radiosensitization of head and neck cancer cells, which responded with FAK dephosphorylation [ 92 ]. In addition, the combination of gemcitabine and hERG1/integrin β1 complex antibody reduced the volume of tumor masses and produced an increase in survival without significant toxic side effects in pancreatic cancer [ 93 ]. However, in melanomas, although the combination of MAPK and PI3K/AKT inhibitors was successfully used in preclinical experiments and early clinical trials, dual-drug resistance was inevitably observed.…”
Section: Clinical Significance Of Integrin β1mentioning
confidence: 99%
“…Importantly, not all Kv11.1 blockers are arrhythmogenic ( Wallis, 2010 ), examples are represented by Verapamil and sertindole ( D’Amico et al, 2013 ). In order to overcome the cardiotoxicity induced by IC blockers different strategies can be applied ( D’Amico et al, 2013 ): i) using non torsadogenic blockers; ii) using state-specific blockers such as R -roscovitine ( Ganapathi et al, 2009 ); iii) using tumour-specific drugs such as CD 160130 ( Gasparoli et al, 2015 ); iv) using monoclonal antibodies ( Iorio et al, 2019 ) and v) using bispecific antibodies directed against tumour-specific macromolecular complexes such as the Kv11.1/β1 integrin complex ( Duranti et al, 2021a ; 2021b ; Iorio et al, 2022 ; Lottini et al, 2023 ).…”
Section: Ion Channels In Human Cancermentioning
confidence: 99%
“…Overall, we favour the possible exploitation of the hERG1-β1 complex as a molecular target for therapeutic purposes with a specific therapeutic antibody (the single-chain diabody hERG1-β1) which impacts on cancer-relevant signalling pathways, such as AKT and HIF-1α, which control proliferation, migration and cancer progression . In this regard, a proper validation of this new tool is mandatory to better outline the possible therapeutic application, alone or in combination with standard drugs such a gemcitabine (Lottini et al, 2022) or bevacizumab (Lottini et al, 2020).…”
Section: Conclusion: the Channel Complexes Landscape In Tumoursmentioning
confidence: 99%